Contemporary paganism listening people, speaking earth - Harvey, Graham (New York Univ. Press, 1997)
"An engaging, broad-based introduction to the main trends of contemporary Paganism, Graham Harvey's book reveals the origins and practical aspects of Druidry, Witchcraft, Heathenism, Goddess Spirituality and Magic, Shamanism and Geomancy, among others, dispelling the unfortunate equation of Paganism with satanism. Making use of both traditional history and the movement's more imaginative sources, the book reveals how Paganism - and its central focus on individual and social life - is evolving and how this 'new religion' perceives and relates to more traditional ones."--BOOK JACKET.